Making Linguistics Matter: Building on the Public's Interest in Language†. Issue 7 (26th July 2013) - Purnell, Thomas; Raimy, Eric; Salmons, Joseph
Abstract Linguists in the United States are acutely aware of the need to engage the public about their work in new and better ways. We describe here our effort to take up that challenge in Wisconsin by building a set of outreach projects that connect with communities throughout the state and that focus on issues of importance to particular audiences. Through these projects, we have become convinced that outreach, teaching, and research — treated separately and distinctly for academic evaluation — are inextricably linked, often to the point of being indistinguishable in practice.